Multi-Criteria Decision Making for Smart City Implementation Using Fuzzy Soft Maut Method - Adem Yolcu; Taha Yasin Öztürk (Winaya Inspirasi Nusantara Foundation, 2025)
Smart city development requires making choices based on multiple and competing criteria. Thus, in these kinds of environment, the opinions of experts are often given in terms of vague language rather than specific numbers. This paper investigates this challenge by developing a Fuzzy Soft Multi-Attribute Utility Theory (MAUT) system for assessing the readiness of metropolitan municipalities to implement a smart city. This is a hybrid method which integrates the parameter-based structured approach of soft sets with the ability to model uncertainty in fuzzy sets and usefulness aggregation rules of MAUT. Triangular fuzzy numbers are employed for the representation of an expert’s judgment. A procedure is followed in order to aggregate, normalize the assessments, and then combine them in an overall utility score. The model is developed to help decision-makers in creating a transparent and flexible method to address numerous criteria in uncertain situations in the context of urban and smart city planning.